Criminal Liability for Perpetrators of Embezzlement in Positions in Finance Companies - Rusli, Tami; Sholihah, Hulwatus (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: The law on the crime of embezzlement in office that occurs within the financing company, especially at PT CIMB Niaga Auto Finance, as a form of abuse of trust due to weak internal supervision, economic pressure, and opportunities for the perpetrator to carry out his position so as to cause losses to the company and damage moral values and legal certainty.Purposes of the Research: To analyze the factors that cause and criminal responsibility of embezzlement perpetrators in office.Methods of the Research: The research method used is normative and empirical juridical by utilizing primary, secondary, and tertiary legal materials through literature studies and field studies in the form of observations and interviews to obtain data relevant to the research problem.Results Main Findings of the Research: The findings of the study show that the crime of embezzlement in office occurs due to trust factors, economic pressure, and great opportunities due to the weak corporate supervision system. The defendant deliberately abused his position as an employee to control and transfer the company's vehicle to another party, causing significant material losses. The elements of Article 374 of the Criminal Code were legally and convincingly proven, and no excuse or justification was found for the defendant. Therefore, the defendant was sentenced to one year and six months in prison and the evidence was returned to PT CIMB Niaga Auto Finance as a form of legal accountability and enforcement of legal certainty.